Aromatic Plants as a Source of Bioactive Compounds - Christaki, Efterpi; Bonos, Eleftherios; Giannenas, Ilias; Florou-Paneri, Panagiota (My University, 2012)
Aromatic plants, also known as herbs and spices, have been used since antiquity as folk medicine and as preservatives in foods. The best known aromatic plants, such as oregano, rosemary, sage, anise, basil, etc., originate from the Mediterranean area. They contain many biologically active compounds, mainly polyphenolics, which have been found to possess antimicrobial, antioxidant, antiparasitic, antiprotozoal, antifungal, and anti-inflammatory properties. Currently, the demand for these plants and their derivatives has increased because they are natural, eco-friendly and generally recognized as safe products. Therefore, aromatic plants and their extracts have the potential to become new generation substances for human and animal nutrition and health. The purpose of this review is to provide an overview of the literature surrounding the in vivo and in vitro use of aromatic plants.
Keywords: aromatic plants; bioactive compounds; polyphenolics